Diversity of Fish Species in Cilodong Lake - Prihatini, Wahyu (Journal of Science Innovare, 2018)
Fish provides many benefits for humans, such as food and ornamental fish. Lake fish in West Java is increasingly threatened due to environmental degradation. This study aimed to record the diversity of fish species and it’s potency in Cilodong Lake, Depok. The parameters measured were the diversity of fish species by Shannon Wienner index, and the physical chemical of water quality that were pH, DO, BOD, COD, TOM, temperature, brightness, and depth. This research found 12 species consumption fishes, and 5 species of ornamental fishes. Four most common species found were Oreochromis mossambicus (cichlids/mujair), Oreochromis sp., Hypostomus sp. (ikan sapu-sapu), and Dermogenys pussil (julung-julung). The Pearson correlation analysis results showed that all physical chemical parameters of water correlated inversely with the diversity of fish species. Parameters that had very strong correlation with the species diversity in Cilodong Lake were the water depth, temperature, and COD. Keywords: Species Diversity, Fish, Lake Cilodong